Knowledge, attitudes and practices on leptospirosis prevention among local communities in Jempol district, Negeri Sembilan, Malaysia - Shing, Wei Ng; Selvarajah, Gayathri Thevi; Bejo, Siti Khairani; Safii, Razitasham; Muhamad Saliluddin, Suhainizam; Mohamad Gobil, Abdul Rahman; Amin Nordin, Syafinaz (Regional Tropical Medicine and Public Health Network, 2019)
Leptospirosis is a major public health problem in Malaysia. We aimed to determine the knowledge, attitudes and practices (KAP) regarding leptospirosis and its prevention among subjects in Negeri Sembilan, Malaysia, a leptospirosis-prone area, in order to inform leptospirosis control and prevention programs. We conducted a cross-sectional study among randomly selected residents in Jempol District, Negeri Sembilan from July 2017 until September 2017. Each subject was intervened using a validated close-ended questionnaire asking about demographics and KAP about leptospirosis and its prevention. Inclusion criteria were those aged ≥18 years residing in the study area who were willing to participate in the study. A total of 260 subjects were included in and completed the questionnaire (61.1% females). Twenty-five percent of subjects had never heard of leptospirosis. Of those who had heard of leptospirosis, 41.2% had a good knowledge level about it. Ninety-three point five percent, 99.2% and 87.7% of subjects had a satisfactory attitude level, a satisfactory general practice level and a satisfactory safe work practice level regarding leptospirosis prevention. There was a significant association between general safe work practices and gender (p< 0.05). In summary, one-fourth of subjects knew nothing about leptospirosis or its prevention. Of those who knew about leptospirosis, KAP levels were relatively high. Leptospirosis control and prevention program in the study area need to continue to try to reach more of the study population. Further studies are needed to determine how best to reach the remaining quarter of the population in the study area who are not aware of leptospirosis and its prevention.